Islamic architecture today and tomorrow : (re)defining the field - Gharipour, Mohammad; Coslett, Daniel E. (Critical studies in architecture of the Middle East., 2022)
"Through Islamic Architecture Today and Tomorrow, established experts, designers, and newer scholars from the world of 'Islamic architecture', broadly conceived, consider the field's changing nature and continued relevance in our rapidly globalizing context. Reflective essays address the meaning of 'Islamic' in built environments, as well as the geographical, chronological, and disciplinary diversity of a dynamic field of study that encompasses far more than mosques and tombs. Essays address the use and interpretation of historic structures and spaces, in addition to contemporary design, conservation, and touristic experience, as well as research, publication, and pedagogical practices. It introduces scholars and practitioners to the state of Islamic architecture as a field of inquiry and provides a snapshot of the issues and challenges facing the field today. Looking forward, it invites readers to consider built environments in Islamic contexts as integral to global systems from an interdisciplinary and inclusive perspective. While this volume offers nuanced perspectives on a host of pressing questions, it ultimately aims to advance a necessarily on-going conversation. The book will have wide appeal among architectural historians, art historians, and other scholars working on material in the traditional Islamic regions of the world (North Africa, the Middle East, and South Asia) and beyond, as well as scholars of religion and society. Practicing architects, landscape architects, planners, preservationists, and heritage managers in the regions addressed may also be interested in the volume. Essays have been written with non-specialist and student readers in mind. Undergraduate, graduate, and design students may use selected essays, or the entire collection, in university or graduate school coursework in architecture and Middle Eastern or Islamic studies"--